Pengaruh Dividen Dan Struktur Modal Terhadap Nilai Perusahaan Pada Perusahaan Retail Yang Terdaftar Di Bursa Efek Indonesia Periode 2018-2022 - Renaldi, Rafli; Alfiana, Alfiana; Pujiyanti, Pujiyanti (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to examine the influence of dividends and capital structure on firm value in retail companies listed on the Indonesia Stock Exchange (IDX) during the 2018–2022 period. The independent variables consist of the Dividend Payout Ratio (DPR) and Debt to Equity Ratio (DER), while firm value is measured using Tobin’s Q (PBV). The sample includes five retail companies: PT Matahari Department Store Tbk (LPPF), PT Ramayana Lestari Santosa Tbk (RALS), PT Ace Hardware Indonesia Tbk (ACES), PT Sumber Alfaria Trijaya Tbk (AMRT), and PT Erajaya Swasembada Tbk (ERAA). The analysis employs a panel data regression model, selected through the Chow Test, Hausman Test, and Lagrange Multiplier Test. All tests indicate that the Random Effect Model (REM) is the most appropriate. Normality assumptions are met, although a high correlation between independent variables indicates potential multicollinearity. The REM results reveal that DPR has a significant positive effect on firm value (p = 0.0006), indicating that higher dividend payments enhance market perception of firm value. Meanwhile, DER shows a significant negative effect (p = 0.0004), suggesting that high leverage reduces firm value. Simultaneously, DPR and DER significantly affect firm value (F-statistic p = 0.004664), with a contribution of 33.03% explained variance. These findings highlight the importance of stable dividend policies and prudent financing decisions to improve firm value in the retail industry, which is highly sensitive to economic changes and consumer demand shifts.